Socioeconomic deprivation and the outcome of pulmonary rehabilitation in England and Wales - Steiner, Michael C.; Lowe, Derek; Beckford, Katy; Blakey, John; Bolton, Charlotte E.; Elkin, Sarah; Man, William D -C.; Roberts, C. Michael; Sewell, Louise; Walker, Paul; Singh, Sally J. (BMJ Publishing Group, 2017)
Background: Pulmonary rehabilitation (PR) improves exercise capacity and health status in patients with COPD, but many patients assessed for PR do not complete therapy. It is unknown whether socioeconomic deprivation associates with rates of completion of PR or the magnitude of clinical benefits bequeathed by PR.